Analisis Pelatihan Merajut Dalam Mengembangkan Potensi Entrepreneurship Mahasiswa Universitas PGRI Wiranegara Pasuruan - Indarti, Nunuk -; Pratiwi, Zulfa Aprilia; Pradikto, Sugeng (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2021)
This study aims to determine; 1) The efforts made by students in developing entrepreneurial potential; 2) The effect of knitting training on the entrepreneurial potential of UNIWARA Students; 3) The results achieved by students with knitting training. This research is a qualitative and data collection technique using interviews. Knitting training plays an important role for students, one of which is to develop skills and explore potential in depth. The results of this training make students enthusiastic about participating in knitting training, because the benefits of this activity can be implemented by creating a knitting product that makes a profit if the product can be sold successfully. The effect of knitting training to develop students' entrepreneurial potential, namely: 1) Increasing the potential for student creativity; 2) Being able to know the potential that exists within oneself; 3) The results of knitting training can be implemented in the community; 4) Creating a work of knitting results; 5) Generate a profit side for works that are successfully sold; 6) Changing the mind set about job opportunities. Based on the results of the research, the researcher gave several recommendations as follows: 1) For students, it is hoped that they will continue to seek experiences at a young age with all the things that can be used. develop creativity. 2) For the next researcher it is suggested to look at other factors that influence entrepreneurial interest such as personality or environment. Alternatively, analyze the factors of interest in knitting training.